Breast Cancer in Men. Case report - Dianarelys Villafuerte Delgado; Olga Lidia Rodríguez Infanzón; Rubén Sánchez Abdala (Revista Finlay)
Breast cancer in men is a rare and infrequent disease, which occurs in a very small proportion with respect to different types of cancers. Such entity is the 0.2 to 1.5 % of all malignant tumors in men. Imaging studies have a very precise diagnostic value in these entities. It is presented the case of a male patient with apparent healthy history who comes the consultation due to palpating a "ball" in the left breast, this patient went to the Imaging Department for conducting a mammography as well performing a study with oblique craniocaudal views and a middle lateral of both nipples. Breast ultrasonography showed a nodular, homogeneous image. It was made a referral to multidiscipline breast consultation with surgical possibilities for the tumor. Due to the infrequent appearance of this entity in men, it is decided to make this case report.